Surface sediment properties and heavy metal pollution assessment in the Shallow Sea Wetland of the Liaodong Bay, China. Issue 1 (15th July 2017) - Wang, Jin; Ye, Siyuan; Laws, Edward A.; Yuan, Hongming; Ding, Xigui; Zhao, Guangming
Abstract: Liaodong Bay, a semi-enclosed bay located in northeastern China, is impacted by the discharges of five rivers. We analyzed 100 surface sediment samples from the Shallow Sea Wetland of Liaodong Bay for grain size and concentrations of organic carbon (Corg) and heavy metals. The ranges of the heavy metal concentrations were 2.32–17 μg/g (As), 0.025–1.03 μg/g (Cd), 18.9–131 μg/g (Cr), 4.6–36.1 μg/g (Cu), 0.012–0.29 μg/g (Hg), 13.7–33.9 μg/g (Pb), and 17.4–159 μg/g (Zn). Pollution assessments revealed that some stations were moderately to highly polluted with As, Cd, and Hg. Severe pollution was apparent in the Xiaoling River estuary; lower concentrations of heavy metals were observed in other river mouths, where the sediments were more coarse. The distributions of the heavy metals were closely associated with Corg and grain size. Highlights: The pollution of surface sediment from the Liaodong Bay, China was assessed. Metals As, Cd, and Hg showed moderate and strong pollution in some stations. Severe pollution was occurred in one of the five river mouths. The concentrations of heavy metals were closely associated with Corg and grain size.